Phylogenetic landscape of Monkeypox Virus (MPV) during the early outbreak in New York City, 2022 - Luz H. Patiño; Susana Guerra; Marina Muñoz; Nicolas Luna; Keith Farrugia; Adriana van de Guchte; Zain Khalil; Ana Silvia Gonzalez-Reiche; Matthew M. Hernandez; Radhika Banu; Paras Shrestha; Bernadette Liggayu; et al. (Emerging Microbes and Infections, 2023)
Monkeypox (MPOX) is a zoonotic disease endemic to regions of Central/Western Africa. The geographic endemicity of MPV has expanded, broadening the human-monkeypox virus interface and its potential for spillover. Since May 2022, a large multi-country MPV outbreak with no proven links to endemic countries has originated in Europe and has rapidly expanded around the globe, setting off genomic surveillance efforts. Here, we conducted a genomic analysis of 23 MPV-infected patients from New York City during the early outbreak, assessing the phylogenetic relationship of these strains against publicly available MPV genomes. Additionally, we compared the genomic sequences of clinical isolates versus culture-passaged samples from a subset of samples. Phylogenetic analysis revealed that MPV genomes included in this study cluster within the B.1 lineage (Clade IIb), with some of the samples displaying further differentiation into five different sub-lineages of B.1. Mutational analysis revealed 55 non-synonymous polymorphisms throughout the genome, with some of these mutations located in critical regions required for viral multiplication, structural and assembly functions, as well as the target region for antiviral treatment. In addition, we identified a large majority of polymorphisms associated with GA > AA and TC > TT nucleotide replacements, suggesting the action of human APOBEC3 enzyme. A comparison between clinical isolates and cell culture-passaged samples failed to reveal any difference. Our results provide a first glance at the mutational landscape of early MPV-2022 (B.1) circulating strains in NYC.